BIOLOGICAL CHARACTERISTICS OF ORIGANUM VULGARE L. - Boboeva Kh. B.; Begmatova M. Kh. (Galaxy International Interdisciplinary Research Journal, 2022)
The Samarkand region is part of the Dalian family of Hypericaceae (Morphological characteristic of Hepericum perfaratum L) and synergism of seeds in Akdarya region of Samarkand at the experimental of Samarkand Agriculture Institute and ecology, botany and plant physiology laboratory, and the following results achieved.